Antibody-Drug Conjugates Targeting the Human Epidermal Growth Factor Receptor Family in Cancers - Yu, Jinfeng; Fang, Tong; Yun, Chengyu; Liu, Xue; Cai, Xiaoqing (Frontiers in Molecular Biosciences, 2022)
Members of the human epidermal growth factor receptor (HER) family, which includes HER1 (also known as EGFR), HER2, HER3 and HER4, have played a central role in regulating cell proliferation, survival, differentiation and migration. The overexpression of the HER family has been recognized as one of the most common cellular dysregulation associated with a wide variety of tumor types. Antibody-drug conjugates (ADCs) represent a new and promising class of anticancer therapeutics that combine the cancer specificity of antibodies with cytotoxicity of chemotherapeutic drugs. Two HER2-directed ADCs, trastuzumane-emtansine (T-DM1) and trastuzumab-deruxtecan (DS-8201a), have been approved for HER2-positive metastatic breast cancer by the U.S. Food and Drug Administration (FDA) in 2013 and 2019, respectively. A third HER2-directed ADC, disitamab vedotin (RC48), has been approved for locally advanced or metastatic gastric or gastroesophageal junction cancer by the NMPA (National Medical Products Administration) of China in 2021. A total of 11 ADCs that target HER family receptors (EGFR, HER2 or HER3) are currently under clinical trials. In this review article, we summarize the three approved ADCs (T-DM1, DS-8201a and RC48), together with the investigational EGFR-directed ADCs (ABT-414, MRG003 and M1231), HER2-directed ADCs (SYD985, ARX-788, A166, MRG002, ALT-P7, GQ1001 and SBT6050) and HER3-directed ADC (U3-1402). Lastly, we discuss the major challenges associated with the development of ADCs, and highlight the possible future directions to tackle these challenges.